Postpartum Opioid Use among Military Health System Beneficiaries - Watters, Julie A.; Banaag, Amanda; Massengill, Jason C.; Koehlmoos, Tracey P.; Staat, Barton C. (American Journal of Perinatology, 2021)
Objective The aim of the study is to evaluate the prevalence and factors associated with opioid prescriptions to postpartum patients among TRICARE beneficiaries receiving care in the civilian health care system versus a military health care facility.Study Design We evaluated postpartum opioid prescriptions filled at discharge among patients insured by TRICARE Prime/Prime Plus using the Military Health System Data Repository between fiscal years 2010 to 2015. We included women aged 15 to 49 years old and excluded abortive pregnancy outcomes and incomplete datasets. The primary outcome investigated mode of delivery and demographics for those filling an opioid prescription. Secondary outcomes compared prevalence of filled opioid prescription at discharge for postpartum patients within civilian care and military care.Results Of a total of 508,258 postpartum beneficiaries, those in civilian health care were more likely to fill a discharge opioid prescription compared with those in military health care (OR 3.9, 95% CI 3.8–3.99). Cesarean deliveries occurred less frequently in military care (26%) compared with civilian care (30%), and forceps deliveries occurred more frequently in military care (1.38%) compared with civilian care (0.75%). Women identified as Asian race were least likely to fill an opioid prescription postpartum (OR 0.79, 95% CI 0.75–0.83). Women aged 15 to 19 years had a lower odds of filling an opioid prescription (OR 0.83, 95% CI 0.80–0.86). Women associated with a senior officer rank were less likely to fill an opioid prescription postpartum (OR 0.83, 95% CI 0.73–0.91), while those associated with warrant officer rank were more likely to fill an opioid prescription (OR 1.14, 95% CI 1.06–1.23).Conclusion Our data indicates that women who received care in civilian facilities were more likely to fill an opioid prescription at discharge when compared with military facilities. Factors such as race and age were associated with opioid prescription at discharge. This study highlights areas for improvement for potential further studies.Key Points
Keywords: military health system; opioid prescription; postpartum; pain